Rupture d’affiliation et continuité de la tradition chez des jeunes convertis à l’Islam au Québec : Une nouvelle anthropologie de la famille - Mossiere, Geraldine (Anthropologica, 2022)
Because they reveal the limits of family identity transmission mechanisms, religious conversions can inform and nuance the generational dynamics that seem to be at the roots of current radicalization movements. Drawing on the experience of Quebecois youth who have chosen to join Islam, I discuss the hypothesis of “generational divide” (Roy 2002) by examining the negotiations, compromises and adjustments that make up their family relationships, particularly around the issue of celebrating Christmas. I show that the moral critique that leads converts to dissociate themselves from the identity heritage bequeathed by their parents actually brings them closer to their grandparents’ family model. This concern to perpetuate a lineage tradition carried by moral values reveals in fact a social and political project based on ideals of conviviality and solidarity.